The effect of short cardio on inhibitory control ability of obese people. Issue 4 (20th November 2017) - Tang, Donghui; Tao, Shuang; Ma, Jinlian; Hu, Peijun; Long, Dan; Wang, Jun; Kong, Dexing
Abstract: To study the effect of short cardio on obese male college students' inhibitory control ability, we investigate difference on brain activation patterns before and after short cardio by analyzing the resting state fMRI data. The experiment results of this study show that short cardio can improve the inhibitory control ability of obese people.